Looking for Links between Natural Fibres' Structures and Their Physical Properties. (6th November 2013) - Everitt, Nicola M.; Aboulkhair, Nesma T.; Clifford, Mike J.
Abstract : Natural fibres have excited growing attention in the last decade since they offer the potential to act as candidates substituting for man-made fibres as composite reinforcements. Their superiority over synthetic fibres is that they are environmentally friendly and biodegradable. Numerous industrial sectors are interested in such composites, including but to name a few the aeronautical and the automotive fields. However natural fibres tend to suffer from large variability in properties compared to the "traditional" man-made fibres, and the performance of their composites often does not conform to that theoretically predicted from single-fibre tests. This study investigates the properties of the single fibres. The mechanical properties of the fibres were correlated to their microstructure. There are factors that were found to contribute to the reported variability, some of which are inherent in the fibres and some are related to testing parameters.